On (p,q)-Starlike Harmonic Functions Defined By Subordination - Hasan BAYRAM; Sibel Yalçın (Al-Qadisiyah Journal of Pure Science, 2021)
We introduce and investigate classes of (p,q)-starlike harmonic univalent functions defined by subordination. We first obtained a coefficient characterization of these functions. We give necessary and sufficient convolution conditions, distortion bounds, compactness and extreme points for the (p,q)-starlike harmonic univalent with negative coefficients.